PENGARUH PENILAIAN KINERJA DAN REWARD TERHADAP PRESTASI KERJA PERAWAT PADA RSIA ERIA BUNDA PEKANBARU - Wayuri, Siti Triya; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of performance appraisal and reward on work performance partially and simultaneously. This study used a questionnaire as a data collection tool that was distributed to 71 respondents in nurses RSIA Eria Bunda Pekanbaru. The data are then processed using descriptive analysis and statistical analysis using SPSS 16.0 by conducting validity, reliability testing, simple linear regression analysis, multiple linear analysis, determination analysis (R2) and hypothesis testing with t test (partial test) and F test (simultaneous test ).The results showed that the first hypothesis testing is performance appraisal on work performance, namely t arithmetic (10, 452)> t table (2.760), meaning that performance appraisal has a significant effect on work performance. Second, the reward is t arithmetic (32, 350)> t table (2.760), meaning that the reward has a significant effect on work performance. Test results F arithmetic (757,712)> F table (3,139), meaning that simultaneously performance evaluation and reward significantly influence work performance.Â Keywords: Performance Appraisal, Reward, Performance Achievement